The Influence of Service Quality and Perceived Ease of Shopping at Shopee on the Intention to Use Shopee Paylater - Johana Dwi Ariwati; Siti Aminah (International Journal of Economics (IJEC), 2023)
This study aims to determine the effect of service quality and perceived ease of shopping on the intention to use Shopee Paylater. The method used in this study is a type of quantitative method with purposive sampling technique. The research sample was 99 people. This study retrieved data through questionnaires that have been distributed to consumers with the criteria of being over 17 years old, already knowing, using, and transacting using the Shopee application, and having used and transacted in the Shopee application with the Shopee PayLater payment method. The analytical tool used in this study is the Partial Least Square (PLS) model and the results of the questionnaire have been declared valid and reliable. The results of this study indicate that service quality has a positive and significant effect on the intention to use Shopee Paylater and perceived ease of use has a positive and significant effect on the intention to use Shopee Paylater.